Resepsi Mahasiswa Universitas Baturaja terhadap Nilai Moral Tokoh Utama dalam Novel Ayat-ayat Cinta Karya Habiburrahman El Shirazy - Nilawijaya, Rita; in, Inawati (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The objective of this study is to find and to obtain a profound understanding of the moral values of the main character in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy as responded by the sixth semester students of Indonesian Language and Literature Education Department (PBSI) Baturaja University The students’ receptions include: (1) students’ responses to religious moral values, (2) students’ responses to the personal moral values, (3) responses responses to social moral values. The data of this qualitative research were obtained through closed questionnaires and interviews. The data collection procedure was done by determining the respondents who have read and understood the novel, spreading the questionnaire, and then conducting the interview, collecting the data, classifying the data, and eventually analyzing the data. The result of the research revealed that the religious moral value of the main character is considered good with the percentage of 9,3%. In addition, the personal and social moral values ??are also considered good with the percentage of 9,0%, and 9,6% respectively. The moral values of the main character may become good examples for the students to develop a strong character in religious, personal, and social moral values.